Mechanobiology and survival strategies of circulating tumor cells: a process towards the invasive and metastatic phenotype - Kurma, Keerthi; Alix-Panabières, Catherine (Frontiers in Cell and Developmental Biology, 2023)
Metastatic progression is the deadliest feature of cancer. Cancer cell growth, invasion, intravasation, circulation, arrest/adhesion and extravasation require specific mechanical properties to allow cell survival and the completion of the metastatic cascade. Circulating tumor cells (CTCs) come into contact with the capillary bed during extravasation/intravasation at the beginning of the metastatic cascade. However, CTC mechanobiology and survival strategies in the bloodstream, and specifically in the microcirculation, are not well known. A fraction of CTCs can extravasate and colonize distant areas despite the biomechanical constriction forces that are exerted by the microcirculation and that strongly decrease tumor cell survival. Furthermore, accumulating evidence shows that several CTC adaptations, via molecular factors and interactions with blood components (e.g., immune cells and platelets inside capillaries), may promote metastasis formation. To better understand CTC journey in the microcirculation as part of the metastatic cascade, we reviewed how CTC mechanobiology and interaction with other cell types in the bloodstream help them to survive the harsh conditions in the circulatory system and to metastasize in distant organs.